Endorsement of Global Product Brands by Global Corporate Brands – A Consumer Perspective Across Nations - Bernhard Swoboda; Carolina Sinning (Management International Review, 2021)
Many multinational corporations use their corporate brand to endorse their products but thereby attract international consumers differently. Therefore, it is important to analyze whether corporations profit from endorsed branding strategies across nations or whether they must rely on country-specific factors. The authors propose a theory-based framework and apply multilevel mediation structural equation modeling with cross-level interactions to analyze the typical direct and indirect effects of global corporate brand image and global product brand image on product purchase intention across nations. The authors rely on hierarchical data from 7660 consumer evaluations of a multinational corporation's global corporate and product brands in 35 countries. Importantly, the results provide insights into country-specific moderators, i.e., the degree of country development and national culture, and the respective country portfolio. They further contribute to the application of theory and show a positive indirect effect of global corporate brand image on product purchase intention via global product brand image across nations. Additionally, a positive, although weaker, direct effect of global corporate brand image on product purchase intention is found. However, the degree of country development and national culture moderate both effects differently. This study provides new theoretical implications and shows that a country portfolio offers concrete hints for managers.
Keywords: 330; Endorsed branding strategy; Global corporate and product brands; Cross-national research; Multilevel structural equation modeling; Sub-branding